'Building back better' and the search for values: critically reclaiming Temple's social thought for a post-pandemic policy landscape. Issue 4 (July 2022) - Baker, Christopher
This article moves beyond William Temple's Christianity and Social Order and gives an outline of its implications for public policy today in the context of religiously inspired terrorism, the global financial crash, COVID-19 and postsecularity.